Employee Ownership as a Corporate Governance Mechanism: Systematic Review of Agency Cost Implications in Capital Structure Theory - Gilang Bhirawa Noraga; Arus Reka Prasetia; Widy Muchamad; Wufron Wufron (Jurnal Wacana Ekonomi, 2026)
This systematic literature review synthesizes empirical evidence on the effects of employee ownership schemes on agency costs between shareholders and bondholders in publicly traded firms, identifies underlying causal mechanisms, and analyzes the implications for capital structure. The review follows the PRISMA 2020 guidelines, with a systematic search of the Scopus database. From 44 identified records, 11 studies passed the quality assessment; 8 of these provided sufficient empirical depth on the integrated employee ownership, agency cost, capital structure linkage and were retained for in-depth synthesis, while the remaining 3 studies are reported as supplementary evidence. Data were synthesized using narrative synthesis combined with thematic analysis and mechanism mapping. The included evidence is concentrated in the Chinese (50%) and French (37.5%) institutional contexts, with no studies from the United States, the United Kingdom, or other Anglo-Saxon markets captured by the search an explicit limitation that constrains external validity. The review reveals an asymmetric pattern: all 8 in-depth studies report that employee ownership consistently reduces equity agency costs through interest alignment, enhanced monitoring, and improved information quality, whereas the evidence on debt agency costs is moderate, context-dependent, and confined to two studies that document a curvilinear (U-shaped) relationship in which moderate levels reduce the cost of debt while excessive levels intensify bondholder concerns. Bondholder, shareholder conflict resolution itself remains substantially under-investigated; this gap is interpreted not as a defect of the review but as a substantive finding about the current state of the field. Employee ownership therefore functions as an effective governance mechanism for equity agency costs but requires careful calibration where bondholder protection is at stake. Critical research gaps were identified in the bondholder perspective, formal causal-mechanism testing, optimal ownership thresholds, long-term effects, and geographic representativeness, each of which is discussed as a priority for future inquiry.